Analisis Sistem Informasi Penggajian Pegawai Instansi Pemerintah Daerah - Nurhalisa Wahab; Arnadi Chairunnas; Nichen, Nichen (Journal of Trends Economics and Accounting Research, 2025)
This researchh aims to analyze the implementation of the accounting informatiion system for employee payroll at the BKKBN Office in Watubangga District, Kolaka Regency. The main focus of the research is to compare the payroll system of civil servants (PNS), which is already digital-based, with that of honorary staff, which is still processed manually.The researcch method used is qualitative, with data collection techniques including observation, interviews, and documentation. The findings reveal that the payroll of civil servants is managed in a structured manner through a centrally integrated system using a digital attendance application (Evisum). Meanwhile, the payroll system for honorary employees still relies on manual attendance and conventional salary calculations by administrative staff. This manual system has weaknesses that may lead to delays, recording errors, and a lack of transparency.Based on these findings, it is recommended that the BKKBN Office of Watubangga develop a simple payroll information system specifically for honorary staff and conduct technical training for administrative personnel to ensure a more efficient and accountable payroll process. This study is expected to serve as an evaluation tool and contribute to the development of accounting information systems in regional government agencies.